2010
DOI: 10.1093/ndt/gfq357
|View full text |Cite
|
Sign up to set email alerts
|

Low-GDP peritoneal dialysis fluid ('balance') has less impact in vitro and ex vivo on epithelial-to-mesenchymal transition (EMT) of mesothelial cells than a standard fluid

Abstract: MC from PD effluent of patients treated with a PD fluid containing low GDP levels show fewer signs of EMT and the respective molecules than MC from patients treated with standard fluid, indicating a better preservation of the peritoneal membrane structure and a favourable outcome in patients using low-GDP fluid. It also confirms the hypothesis that the protection of EMT by GDP-reduced fluids is also present in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 27 publications
4
71
1
1
Order By: Relevance
“…Two among the final 12 studies were performed by Kim et al One showed the result at 12 months and the more recent study showed the result at 24 months with the same patients (28). Therefore, we applied the result only at 24 months, and the SR was conducted on the final 11 studies (1,034 patients) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)43,44) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Two among the final 12 studies were performed by Kim et al One showed the result at 12 months and the more recent study showed the result at 24 months with the same patients (28). Therefore, we applied the result only at 24 months, and the SR was conducted on the final 11 studies (1,034 patients) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)43,44) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The potential mechanisms whereby conventional dialysate might drive membrane injury are many and include nonphysiological pH (acidic, typically 5.2), lactate buffer, increased osmolality, high glucose concentrations, and high glucose degradation product (GDP) concentrations. The evidence that low GDP solutions are associated with preservation of mesothelium cells is reasonably compelling from biomarker studies, in particular the increase in dialysate CA-125 levels associated with the use of all the tested biocompatible solutions so far (35) and in one case evidence for reduced epithelial to mesenchymal transition in their morphologic appearance (36). However in our study when patients are compared in terms of biocompatibility of solutions high transporter number was high in conventional solution group but this difference was not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…This results in damage to the peritoneum and alters the peritoneal structure and transportation function. Finally, peritoneal ultrafiltration failure occurs resulting in failure of PD (8). Peritoneal fibrosis is also one of the main causes of PD failure.…”
Section: Discussionmentioning
confidence: 99%